2012
DOI: 10.1088/0957-4484/23/27/275605
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of S-doped graphene by liquid precursor

Abstract: Doping is a common and effective approach to tailor semiconductor properties. Here, we demonstrate the growth of large-area sulfur (S)-doped graphene sheets on copper substrate via the chemical vapor deposition technique by using liquid organics (hexane in the presence of S) as the precursor. We found that S could be doped into graphene's lattice and mainly formed linear nanodomains, which was proved by elemental analysis, high resolution transmission microscopy and Raman spectra. Measurements on S-doped graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(119 citation statements)
references
References 28 publications
(37 reference statements)
6
113
0
Order By: Relevance
“…possible to synthesise S-doped graphene by a chemical vapour deposition approach using a solution of elemental sulphur in hexane as the precursor. 130 As can be derived from data published by Yang et al, another way to obtain sulphurdoped graphene is to blend graphene oxide homogeneously with benzyl disulde, followed by subsequent annealing (compare the scheme in Fig. 4).…”
Section: S-doped Graphene Based Materials For Orrmentioning
confidence: 99%
“…possible to synthesise S-doped graphene by a chemical vapour deposition approach using a solution of elemental sulphur in hexane as the precursor. 130 As can be derived from data published by Yang et al, another way to obtain sulphurdoped graphene is to blend graphene oxide homogeneously with benzyl disulde, followed by subsequent annealing (compare the scheme in Fig. 4).…”
Section: S-doped Graphene Based Materials For Orrmentioning
confidence: 99%
“…For example, synthesis of N-or B-doped graphene has been well studied especially for the application as semiconductor materials [8,14,15]. By contrast, S-doping is generally considered more difficult due to its larger atom compared with C atom [16]. Over about the past three years, researchers have successfully produced S-doped graphene using chemical vapor deposition technology or reaction between graphene (or GO and its derivatives) and S-containing precursors [5,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 27.3 nm for graphene on Cu from hexane as liquid precursor has been reported in the work [27]. Guermoune et al [22] received higher values (168 nm) for graphene obtained on Cu from ethanol precursor but in markedly lower temperatures.…”
Section: Stress Distribution In Graphene Crystalmentioning
confidence: 83%
“…Another liquid carbon precursor found in a recent scientific literature is hexane [25,26]. Gao et al [27] showed the synthesis of S-doped graphene on Cu versus regular one from hexane. In a recent work, Gan et al [28] demonstrated a ternary Cu 2 NiZn alloy as a substrate and compared it to Cu and Cu/Ni.…”
Section: Introductionmentioning
confidence: 99%